5-methoxytryptophan alleviates liver fibrosis by modulating FOXO3a/miR-21/ATG5 signaling pathway mediated autophagy. Issue 7 (3rd April 2021) - Tong, Ming; Zheng, Qing; Liu, Meng; Chen, Liang; Lin, Yi-He; Tang, Shi–Gang; Zhu, Yi-Min
ABSTRACT: Liver fibrosis is a critical health issue in the world due to its rapidly increasing prevalence. It is of great demand to develop effective drugs for the treatment of liver fibrosis. 5-methoxytryptophan (5-MTP) has been reported to play an important role in anti-inﬂammatory, anti-cancer, myocardial-protective eﬀects. However, the anti-fibrotic eﬀect of 5-MTP is never covered in liver. Here, we investigated anti-fibrotic effects of 5-MTP on liver fibrosis and its underlying mechanism. In vitro, 5-MTP treatment could inhibit TGF-β1-induced elevated levels of collagen I, collagen III, fibronectin and α-smooth muscle actin (SMA) by stimulating autophagy process. Mechanically, the expression of FOXO3a was enhanced by 5-MTP and then repressed the level of miR-21, eventually leading to a restoration of autophagy-related gene ATG5. Furthermore, rescue experiments showed 5-MTP could activate autophagy process and suppress the activation of LX-2 cells by regulating FOXO3a/miR-21/ATG5 pathway. Consistently, 5-MTP significantly attenuated CCl4-induced hepatic fibrosis in rat model. In conclusion, our research discovered that 5-MTP effectively alleviated liver fibrosis in vitro and in vivo, which provided new insights into the application of 5-MTP for liver fibrosis.